Care Tasks and Caregiver Burden Among Family Caregivers of Patients With Mental Disorders in China: Illness Perception as a Mediator and Social Support as a Moderator. - Huang, Zhuoer; Yi, Qifeng; Yao, Hao; Li, Kunmei; Li, Chuan; Shi, Yimeng; Hu, Shuang; Chen, Jianhua; Xu, Yifeng (Journal of Psychiatric & Mental Health Nursing (John Wiley & Sons, Inc.), 2025)
Introduction: Caring for a family member with mental disorders is burdensome, which may not only damage the caregivers' well‐being and health, but also hinder patients' recovery. It is critical to investigate the underlying mechanisms for caregiver burden. Aim: To examine the mediating effect of illness perception and the moderating function of social support on the association between care tasks and caregiver burden. Method: A total of 1169 family caregivers of patients with mental disorders were recruited via convenience sampling across China. Data were collected using acceptable reliability scales (Cronbach's α > 0.6). The relationships among care tasks, illness perception, social support and caregiver burden were examined in the SPSS PROCESS macro. Results: Illness perception partially mediates the relationship between care tasks and overall caregiver burden, personal strain and role strain, while social support only alleviates the impact of care tasks on personal strain but not on role strain. Discussion: Care tasks could positively predict caregiver burden. As a mediating moderating mechanism, illness perception and social support could further explain how care tasks affect caregiver burden. Implications for Practice: Psychiatric nurses should provide psychoeducation for family caregivers of patients with mental illness to improve their negative illness perception, as well as increase their social support.